Integrating Higher Order Thinking Skills (HOTS) into English language teaching for elementary school students : teachers' perspectives and challenges - Astrid, Annisa; Amalia Hasanah; Syafryadin (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this research was to 1) identify teachers' perspectives on incorporating HOTS into EFL classes for primary school students and 2) discover the challenges faced by the teachers during the implementation of HOTS based learning. This study used an embedded mixed technique. The quantitative data were acquired by giving one set of closed-response questionnaire items to 39 English teachers teaching English in elementary schools in Palembang, Indonesia. Meanwhile, qualitative data were gathered through one-on-one in-depth interviews with ten English teachers who agreed to be interviewed. The descriptive statistics analysis was used to assess the students' replies to each questionnaire item. Meanwhile, thematic analysis was used to assess the qualitative data gleaned from the interviews. The statistical study revealed that first, Teachers expressed their positive experiences implementing HOTS-based learning in EFL classes for elementary school students. Second, there are five impediments that instructors encountered while applying HOTS-based learning for primary school children; 1) time limitations; 2) supplementing HOTS-based learning resources; 3) selecting an effective teaching strategy to elicit students' HOTS; 4) selecting an effective teaching technique to elicit students' HOTS; 5) Mixed ability of students and 6) Big class size.